Ecological restoration in the Pannonian Basin: evaluation of native species performance and implications for adaptive landscape planning - Caković Milosavljević, Milica; Beloica, Jelena; Čavlović, Dragana (Frontiers in Environmental Science, 2026)
Ecological restoration in protected areas plays a key role in halting biodiversity loss, particularly within the context of global and national biodiversity targets. This study evaluates the success of a restoration project implemented in the buffer zone of the Special Nature Reserve “Ludaš Lake” and Nature Park “Palić”, encompassing wetland and Pannonian forest-steppe habitats, potentially contributing to the resilience of the landscape in the face of ongoing climate change. The goal was to restore degraded habitats using functionally diverse native plant species to enhance ecological stability. This study evaluated the effectiveness of the initial restoration phase, focusing on a 3-year assessment of the survival and establishment of 6,310 planted native tree and shrub seedlings. The monitoring of the initial restoration phase evaluated the performance of 29 planted native species. It also aimed to identify challenges in planning and implementation and to determine which species show the best adaptation to local conditions. Climate projections, a dynamic soil–vegetation model, and the Habitat Suitability Index were used to evaluate species’ future persistence. Results from the initial monitoring phase (3-year period), indicate that Acer campestre, Acer tataricum, Ulmus minor, Prunus spinosa, Prunus tenella, Viburnum lantana, and Ligustrum vulgare exhibited the highest survival rates. According to projections, shrub communities will dominate, with a limited persistence of tree species. The restoration approach presented in this study supports climate-adapted species selection and provides practical guidance for planning restoration in ecologically sensitive and climatically vulnerable areas.